(untitled) (Ágora de Heterodoxias, 2021)
This text presents the central ideas of the author, as a synthesis, on leadership and management in the context of the new realities, under the perspective of complexity as a transdisciplinary construction and having as a guiding thread how to promote transforming changes in democratic and complex social environments.